2022
DOI: 10.1021/acs.energyfuels.2c01762
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic System of Zwitterionic/Anionic Surfactants with Ultralow Interfacial Tension and High Salt Resistance for Enhancing Heavy Oil Recovery

Abstract: Conventional water flooding strategy has limited the further development of heavy oil recovery due to the lower displacement efficiency. In this work, a potential zwitterionic/anionic surfactant system to enhance heavy oil recovery in the high salinity was proposed through low budget and feasible mixing. We evaluated the capabilities of the mixed surfactant systems consisting of zwitterionic cocoamidopropyl sulfonate betaine (CSB) and anionic sodium dodecyl benzene sulfonate (SDBS) in terms of surface tension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…83 Chen et al 84 combined the advantages of dilution and surfactant addition, using a toluene in water emulsion stabilized by AES− DOA mixed surfactants to emulsify extra-heavy oil. Ma et al 85 proposed a salt-tolerant zwitterionic/anionic surfactant system with enhanced heavy oil recovery, which will produce synergistic effects and form smaller droplets (0.1−3 μm) to stabilize heavy oil emulsions. Yu et al, 28 using a fine emulsion system, found tha it exhibits well-plugging and sweep-volumeenlargement behaviors.…”
Section: Emulsification and Viscosity Reductionmentioning
confidence: 99%
“…83 Chen et al 84 combined the advantages of dilution and surfactant addition, using a toluene in water emulsion stabilized by AES− DOA mixed surfactants to emulsify extra-heavy oil. Ma et al 85 proposed a salt-tolerant zwitterionic/anionic surfactant system with enhanced heavy oil recovery, which will produce synergistic effects and form smaller droplets (0.1−3 μm) to stabilize heavy oil emulsions. Yu et al, 28 using a fine emulsion system, found tha it exhibits well-plugging and sweep-volumeenlargement behaviors.…”
Section: Emulsification and Viscosity Reductionmentioning
confidence: 99%